Выделение тепла приливного трения на стадии формирования Земли - Хачай, Ю.В.; Хачай, О.А.; Антипин, А.Н. (Геоінформатика, 2017)
Современные исследования показали важность учета вклада внутренних источников энергии и процессов тепломассопереноса во внутренние оболочки протопланеты и их влияния на динамику формирования Земли. В качестве основных рассматриваются вклады потенциальной энергии, сопровождающей формирование конденсированного тела из протопланетного облака; энергии естественного радиоактивного распада короткоживущих радиоактивных элементов и энергии гравитационного сжатия. Однако следует обратить внимание на то, что формирование Земли происходило по сути в двойной системе Земля-Луна. Поэтому важно учитывать выделение энергии вязкого трения лунных приливов, которое существенно изменялось на стадии вещественной аккумуляции системы. Предложенная ранее модель дифференциации вещества Солнечного протопланетного облака в процессе вещественной аккумуляции планет земной группы опирается на численные результаты решения краевой задачи для системы уравнений, описывающей баланс импульса энергии, массы, температуры и давления во внутренних областях растущих Земли и Луны. Сучасні дослідження показали важливість урахування внеску внутрішніх джерел енергії і процесів тепломасоперенесення у внутрішні оболонки протопланети і їх впливу на динаміку формування Землі. Як основні розглянуто внески потенціальної енергії, що супроводжує формування конденсованого тіла з протопланетної хмари; енергії природного радіоактивного розпаду короткоіснуючих радіоактивних елементів і енергії гравітаційного стиснення. Втім слід звернути увагу на те, що формування Землі відбувалося по суті у подвійній системі Земля—Місяць. Тому важливо враховувати виділення енергії в’язкого тертя місячних припливів, яке істотно змінювалося на стадії акумуляції системи. Модель диференціації речовини Сонячної протопланетної хмари в процесі речовинної акумуляції планет земної групи, яку запропоновано раніше, ґрунтується на чисельних результатах розв’язку крайової задачі для системи рівнянь, що описує баланс імпульсу енергії, маси, температури і тиску у внутрішніх зонах зростаючих Землі і Місяця. Purpose Modern studies have shown the importance of taking into account the contribution of internal energy sources and heat-mass transfer processes in the inner shells of the protoplanet and their influence on the dynamics of the formation of the Earth in the process of its accumulation [1, 5]. Among the major contributors are the potential energy accompanying the formation of a condensed body from a protoplanetary cloud, the energy of naturally radioactive decay of short-lived radioactive elements, and the energy of gravitational compression. However, attention should be paid to the fact that the formation of the Earth took place essentially in the binary system Earth-Moon. Therefore, it is important to take into account the energy release of viscous friction of the lunar tides, which changed significantly during the accumulation phase of the system. In [1, 5], a model for the differentiation of the substance of the solar protoplanetary cloud was proposed in the process of accumulation of terrestrial planets based on the obtained numerical results of the solution of the boundary value problem for a system of equations describing the balance of momentum, mass, temperature and pressure in the inner regions of the growing Earth and Moon in the process of their accumulation (1)—(5).
Design/ methodology/ approach In order to investigate the problem, we used the numerical solution of boundary value problems for the 3D system of differential equations. We constructed a non-uniform difference grid for time and space variables and used a standard implicit difference scheme. An iterative process was constructed, which begins with the solution of equation (1), from which the time step is located. Then we included the solution of the problems for equation (2)—(3) with the values of the coefficients in equations (2)—(3) and (6)—(9) calculated from the values at the previous stage, and the internal iteration cycle. After the specified relative accuracy is achieved, a step is taken along the selected radius, and an external cycle is started.
Findings From the above, the following qualitative estimates can be obtained. Since the angular velocity of the orbital motion of the satellite is much greater than the angular velocity of the planet’s own rotation, it follows from the law of conservation of angular momentum (6) that the tidal interaction with increasing mass of the central body ensures the transfer of the orbital angular momentum of the satellite to the central massive body. Consequently, losing the orbital moment, the satellite must approach the central body right up to the Roche orbit. The problem of the behavior of a satellite at the Roche limit requires a careful mathematical study. Due to the continuing transfer of the satellite’s orbital moment to the central body, its own angular velocity continues to grow. This should lead to an increase in the orbital angular velocity of the satellite and an increase in the radius of its orbit, which is observed up to the present time. Thus, the effect of dissipation of viscous friction must have manifested itself at the stage of formation of the outer core of the Earth. The results obtained depend on the parameters, primarily, the viscosity versus temperature and pressure, the values of which are known with a high degree of uncertainty. They are to be clarified as a result of further physical-mathematical and indirect geological research.
Practical value/ implications The results obtained will serve as a basis for constructing new systems of differential equations of Earth’s dynamics at the stage of planetary accumulation, as well as revealing the role of the energy dis¬sipation of viscous friction in the differentiation processes of the matter of the interior envelopes of the Earth at the stage of its formation, which provided the features of the MHD processes of the Earth’s dynamo and metallogeny of the Earth’s lithosphere.